Pregunta
upstudy study bank question image url

Solve \( 6 x(x+2)=-42 \) by completing the square \( x=\square \)

Ask by Little Li. in the United States
Nov 12,2024

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

No real solutions.

Solución

Solve the equation \( 6x(x+2)=-42 \). Solve the equation(The complex numbers system) by following steps: - step0: Solve using the quadratic formula in the complex numbers system: \(6x\left(x+2\right)=-42\) - step1: Expand the expression: \(6x^{2}+12x=-42\) - step2: Move the expression to the left side: \(6x^{2}+12x+42=0\) - step3: Solve using the quadratic formula: \(x=\frac{-12\pm \sqrt{12^{2}-4\times 6\times 42}}{2\times 6}\) - step4: Simplify the expression: \(x=\frac{-12\pm \sqrt{12^{2}-4\times 6\times 42}}{12}\) - step5: Simplify the expression: \(x=\frac{-12\pm \sqrt{-864}}{12}\) - step6: Simplify the expression: \(x=\frac{-12\pm 12\sqrt{6}\times i}{12}\) - step7: Separate into possible cases: \(\begin{align}&x=\frac{-12+12\sqrt{6}\times i}{12}\\&x=\frac{-12-12\sqrt{6}\times i}{12}\end{align}\) - step8: Simplify the expression: \(\begin{align}&x=-1+\sqrt{6}\times i\\&x=\frac{-12-12\sqrt{6}\times i}{12}\end{align}\) - step9: Simplify the expression: \(\begin{align}&x=-1+\sqrt{6}\times i\\&x=-1-\sqrt{6}\times i\end{align}\) - step10: Rewrite: \(x_{1}=-1-\sqrt{6}\times i,x_{2}=-1+\sqrt{6}\times i\) - step11: Remove the complex number(s): \(\textrm{No real solution}\) The equation \(6x(x+2)=-42\) does not have any real solutions. Therefore, there is no value of \(x\) that satisfies the equation.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Extra Insights

To solve the equation \( 6x(x + 2) = -42 \), let's first rearrange it into a standard form. We can simplify it by dividing both sides by 6: \[ x(x+2) = -7 \] Now, expand the left side: \[ x^2 + 2x + 7 = 0 \] To solve this by completing the square, we move the constant to the other side: \[ x^2 + 2x = -7 \] Next, we'll complete the square on the left side. Take half of the coefficient of \(x\) (which is 2), square it (getting 1), and add it to both sides: \[ x^2 + 2x + 1 = -7 + 1 \] This simplifies to: \[ (x + 1)^2 = -6 \] Now, take the square root of both sides: \[ x + 1 = \pm i\sqrt{6} \] Isolating \(x\): \[ x = -1 \pm i\sqrt{6} \] So the solutions are: \[ x = -1 + i\sqrt{6} \quad \text{and} \quad x = -1 - i\sqrt{6} \]

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad